(untitled) (Proceedings of the Society of Antiquaries of Scotland, 1923)
The usual business was conducted at the Anniversary meeting, including the election of new Fellows and the presentation of a list of deceased Fellows. Other reports presented included: A report on the number of Fellows on the Society’s Roll Brief obituaries for some of the Fellows who died in the previous year A report on the progress of the Society’s forthcoming publications A report on the items added to the Society’s museum and library collections over the previous session A report on the Society’s excavations in Scotland A note on the Rhind Lectures Treasurer then presented the Annual Report on the Society’s finances. Meeting notes for 11 December, 1922 are appended.